Reconfigurable free-space optical cores for storage area networks. - Wilkinson, Tim D. (IEEE Communications magazine)
The role of the optical storage area network is becoming increasingly important in computer network architectures, with the amount of information being presented and requested on the Internet ever increasing. One of the key questions is what is the role of, and how do we control, an optical switch core within a SAN to optimize its performance. In this article we review two potential optical switch technologies and assess their performance as a SAN optical switch core.